Insulated wire

By using a laminated structure of a fluororesin layer and a PAEK resin layer in the coating layer of the insulated wire, the problem of lowering the dielectric constant of the coating layer but insufficient damage resistance and varnish affinity in the prior art is solved, and high-performance and miniaturized insulated wires are achieved.

CN119816903APending Publication Date: 2025-04-11DAIKIN INDUSTRIES LTD

Patent Information

Application Number
CN202380062282.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-08-28
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The coating of the conventional insulated wires is difficult to improve damage resistance and affinity with varnish while reducing the dielectric constant. Especially in the case of high voltage and miniaturization requirements, there are problems such as damage to insulation characteristics and varnish repulsion.

Method used

The coating layer is formed by a laminated structure of a fluororesin layer and a PAEK resin layer. The fluororesin layer contains a fluororesin that can be melt-processed, and the PAEK resin layer contains a polyaryl etherketone (PAEK) resin to ensure that the dielectric constant of the coating layer is low and damage-resistant.

Benefits of technology

The low dielectric constant of the coating is achieved, the non-prone damage and good affinity with the varnish, ensuring high performance and miniaturization application capabilities of insulated wires.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005287336850000111
    Figure BDA0005287336850000111
  • Figure BDA0005287336850000251
    Figure BDA0005287336850000251
  • Figure BDA0005287336850000261
    Figure BDA0005287336850000261
Patent Text Reader

Abstract

Provided is an insulated wire provided with a conductor and a coating layer formed around the conductor, the coating layer being provided with: a fluororesin layer containing a melt-processable fluororesin; and a PAEK resin layer formed around the fluororesin layer and containing a polyaryletherketone (PAEK) resin, the coating layer having a thickness of 40 [mu] m to 300 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to insulated wires. Background Art

[0002] Patent document 1 describes an insulated wire having an insulating coating formed by stacking at least two insulating layers on a rectangular cross-section conductor, characterized in that the stacked insulating coating is composed of an enameled insulating layer containing a thermosetting resin located on the outer periphery of the conductor and an extruded insulating layer containing a thermoplastic resin located on the outer side of the layer, the thickness of the enameled insulating layer is greater than 50 μm, and the thickness (T) of the entire stacked insulating coating and the relative dielectric constant (ε) at 100°C, the maximum thickness (Tmax) of one of the stacked insulating layers, and the maximum value (εmax) and minimum value (εmin) of the relative dielectric constant at 100°C satisfy all of the following relationships.

[0003] T≥100μm (1.1)

[0004] Tmax≤100μm (1.2)

[0005] 1.5≤ε≤3.5 (2.1)

[0006] 1.0≤εmax / εmin≤1.2 (2.2)

[0007] Patent Document 2 describes a flat magnetic wire having a flat conductor and a coating layer, wherein the coating layer is formed around the flat conductor and is formed of a heat shrinkable tube for forming a flat magnetic wire coating layer containing a copolymer containing tetrafluoroethylene units and fluoroalkyl vinyl ether units.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: International Publication No. 2017 / 175516

[0011] Patent Document 2: Japanese Patent Application Publication No. 2021-2458 Summary of the invention

[0012] Problems to be solved by the invention

[0013] An object of the present disclosure is to provide an insulated wire having a coating layer that has a low dielectric constant, is not easily damaged, and does not repel varnish.

[0014] Means for solving problems

[0015] According to a first aspect of the present disclosure, there is provided an insulated wire comprising a conductor and a covering layer formed around the conductor, wherein the covering layer comprises: a fluororesin layer containing a melt-processable fluororesin; and a PAEK resin layer formed around the fluororesin layer and containing a polyaryletherketone (PAEK) resin, wherein the thickness of the covering layer is 40 μm to 300 μm.

[0016] Effects of the Invention

[0017] According to the present disclosure, it is possible to provide an insulated wire having a coating layer that has a low dielectric constant, is not easily damaged, and does not repel varnish. DETAILED DESCRIPTION

[0018] Hereinafter, specific embodiments of the present disclosure will be described in detail, but the present disclosure is not limited to the following embodiments.

[0019] Patent Document 1 states that in order to improve the performance of a rotating machine such as a motor, it is required to accommodate a larger number of windings in the slots of a stator. In addition, Patent Document 1 states that, as an insulated wire for such a winding, an insulated wire having an insulating coating formed by laminating at least two insulating layers on a rectangular cross-section conductor is described, and that the laminated insulating coating is composed of an enameled insulating layer containing a thermosetting resin located on the outer periphery of the conductor and an extruded insulating layer containing a thermoplastic resin located outside the enameled insulating layer.

[0020] Patent document 2 describes a flat magnetic wire comprising a flat conductor and a coating formed around the flat conductor, wherein the coating is formed of a heat shrinkable tube for forming a flat magnetic wire coating containing a copolymer containing tetrafluoroethylene units and fluoroalkyl vinyl ether units.

[0021] However, in the composition of the coating of the existing insulated wire, it is difficult to improve the damage resistance and affinity with varnish while reducing the dielectric constant of the coating. In the motor used in electric vehicles, there is a trend of increasing the use voltage for the purpose of miniaturization and high performance. With the high voltage, a higher partial discharge starting voltage is required for the coated wire used in the motor than before, and in order to achieve miniaturization, the coating of the insulated wire is preferably thin. In the formation of the coating, it is preferred to use a material with a low dielectric constant. However, if a material with a low dielectric constant is used to form a relatively thin coating, the coating is easily damaged when the coating is inserted into the slot of the iron core of the rotating motor, and there is a problem of impaired insulation properties. Furthermore, when the insulated wire has a flat conductor, when the insulated wire is bent in the side direction, it is necessary to use a metal clamp to apply a large load to bend, but at this time the coating is easily damaged, and there is a problem of impaired insulation properties. In addition, the insulated wire is sometimes fixed to the core using an impregnation varnish containing epoxy resin or the like, but there is a problem that the coating layer using a material having a low dielectric constant repels the varnish and it is difficult to fix the insulated wire to the core.

[0022] In contrast, the insulated wire of the present invention has a coating layer formed by a laminated structure including a fluororesin layer containing a melt-processable fluororesin and a PAEK resin layer containing a polyaryletherketone (PAEK) resin, so that the dielectric constant of the coating layer is sufficiently low, and the coating layer is not easily damaged when inserted into a slot of an iron core of a rotating electric machine or when bent along the side, and the coating layer is fully fused to the impregnation varnish. Therefore, the insulated wire of the present invention can be easily deformed into a shape that can be easily accommodated in a slot without impairing good insulation properties, and can be easily fixed to the iron core, so that the miniaturization and high performance of rotating electric machines such as motors can be achieved.

[0023] The insulated wire of the present disclosure includes a conductor and a coating layer formed around the conductor. Next, the configurations of the conductor and the coating layer will be described in more detail.

[0024] (conductor)

[0025] conductor

[0026] The conductor may be a single wire, a group of wires, a twisted wire, etc., preferably a single wire. The cross-section of the conductor may be in the shape of any of a circle, an ellipse, a rectangle, a square, and a polygon.

[0027] The conductor is not particularly limited as long as it is made of a conductive material, and can be made of materials such as copper, copper alloy, aluminum, aluminum alloy, iron, silver, nickel, etc., preferably at least one selected from the group consisting of copper, copper alloy, aluminum and aluminum alloy. In addition, a conductor plated with silver plating, nickel plating, etc. can also be used. As copper, oxygen-free copper, low-oxygen copper, copper alloy, etc. can be used.

[0028] When the cross section of the conductor is approximately rectangular, that is, when the conductor is a flat conductor, the width of the cross section of the conductor can be 1 mm to 75 mm, and the thickness of the cross section of the conductor can be 0.1 mm to 10 mm. The shape of the cross section of the conductor can be rectangular. The outer diameter of the conductor can be 6.5 mm or more and 200 mm or less. In addition, the ratio of width to thickness can be greater than 1 and less than 30.

[0029] When the cross section of the conductor is substantially circular, that is, when the conductor is a round conductor, the diameter of the conductor is preferably 0.1 mm to 10 mm, more preferably 0.3 mm to 3 mm.

[0030] From the viewpoint of more firmly adhering the conductor to the fluororesin layer, the surface roughness Sz of the conductor is preferably 0.2 μm to 12 μm, more preferably 1 μm or more, further preferably 5 μm or more, and more preferably 10 μm or less.

[0031] The surface roughness of the conductor can be adjusted by treating the conductor using a surface treatment method such as etching, sandblasting, or laser treatment. In addition, the surface of the conductor can also be provided with concavities and convexities by surface treatment. The smaller the distance between the concavities and convexities, the better, for example, 0.5 μm or less. In addition, regarding the size of the concavities and convexities, for example, the area of ​​each concave portion when the convex portion relative to the unprocessed surface is cut is 0.5 μm. 2 The concavoconvex shape may be a single concavoconvex shape of a crater, or may be branched into an ant's nest shape.

[0032] (Coating layer)

[0033] The coating layer is formed around the conductor and includes a fluororesin layer and a PAEK resin layer.

[0034] From the viewpoint of insulation properties, the thickness of the coating layer is preferably 40 μm to 300 μm, more preferably 50 μm or more, further preferably 60 μm or more, more preferably 250 μm or less, further preferably 200 μm or less.

[0035] From the perspective of insulation properties, the relative dielectric constant of the coating layer is preferably 2.9 or less, more preferably 2.7 or less, further preferably 2.5 or less, particularly preferably 2.4 or less, and preferably 1.8 or more. The relative dielectric constant is a value obtained by measuring the changes in the resonant frequency and the electric field strength at a temperature of 20°C to 25°C using a network analyzer HP8510C (manufactured by Hewlett-Packard Co.) and a cavity resonator.

[0036] From the viewpoint of insulation properties, the ratio of the mass of the fluororesin layer in the covered electric wire to the mass of the insulated electric wire is preferably 50 mass % or more, more preferably 55 mass % or more, further preferably 70 mass % or more, and is preferably 95 mass % or less, more preferably 90 mass % or less.

[0037] From the viewpoint of insulation properties, the partial discharge inception voltage of the insulated wire measured at 25° C. preferably satisfies the following relationship.

[0038] Partial discharge inception voltage (V) ≥ 2.2 × X + 810

[0039] X: Ratio of the mass of the fluororesin layer to the mass of the insulated wire (mass %)

[0040] The partial discharge inception voltage of the insulated wire is preferably not easily changed even when the temperature changes. The change rate calculated by the following formula from the partial discharge inception voltage measured at 25°C and the partial discharge inception voltage measured at 200°C of the insulated wire is preferably less than 10%, more preferably less than 5%.

[0041] Change rate (%) = [(partial discharge inception voltage measured at 25°C) - (partial discharge inception voltage measured at 200°C)] / (partial discharge inception voltage measured at 25°C) × 100

[0042] The partial discharge inception voltage of the insulated wire is preferably not easily changed even after the insulated wire is used for a long time at high temperature. The change rate calculated by the following formula between the partial discharge inception voltage measured at 25°C of the insulated wire and the partial discharge inception voltage measured at 25°C after heating the insulated wire at 200°C for 1000 hours is preferably less than 10%, more preferably less than 5%.

[0043] Change rate (%) = [(partial discharge inception voltage measured at 25°C after heating the insulated wire at 200°C for 1000 hours) - (partial discharge inception voltage measured at 25°C)] / (partial discharge inception voltage measured at 25°C) × 100

[0044] The "partial discharge inception voltage measured at 25° C." refers to the partial discharge inception voltage of an insulated wire that has not been heated at 200° C. or higher for one hour or longer.

[0045] In one embodiment of the insulated wire, it is preferred that the thickness of the PAEK resin layer is 15 μm or more, and the load for conducting electricity is 1500 g or more.

[0046] The load to achieve energization is the force (g) when conduction is generated between the needle and the conductor by rubbing the surface of the coating of the insulated wire with a needle to which a continuously increasing force is applied. By configuring the coating of the insulated wire so that the load to achieve energization is 1500g or more, the wear resistance of the coating is improved, and when the coating of the insulated wire is inserted into the slot of the iron core of the rotating electric machine or when the insulated wire is bent in the side direction, a coating that is less likely to be damaged can be obtained. The load to achieve energization can be measured according to the method described in JIS C3216-3.

[0047] (Fluororesin layer)

[0048] The fluororesin layer is formed around the conductor, and a PAEK resin layer is formed on the periphery of the fluororesin layer. The coated electric wire disclosed in the present invention has such a structure, so when a large load is applied to the metal clamp and the coated electric wire is bent, or when the coated electric wire is inserted into the slot of the iron core, the fluororesin layer will not contact the clamp, the slot and other components. Therefore, the fluororesin layer will not be damaged, and it can be easily deformed into a shape that is easily accommodated in the slot while maintaining the excellent electrical properties of the fluororesin layer, and then the coated electric wire can be smoothly inserted into the slot of the iron core. In addition, by impregnating the coated electric wire with varnish, the varnish can be attached to the PAEK resin layer with excellent affinity with the varnish, rather than to the fluororesin layer with poor affinity with the varnish, so the coated electric wire inserted into the slot can be easily fixed to the iron core.

[0049] The fluororesin layer contains a melt-processable fluororesin. In the present disclosure, melt-processability means that the polymer can be melted and processed using existing processing equipment such as an extruder and an injection molding machine. Therefore, the melt-processable fluororesin generally has a melt flow rate of 0.01 g / 10 minutes to 500 g / 10 minutes as measured by the measurement method described below.

[0050] The melt flow rate of the fluororesin is preferably 0.1 g / 10 min to 120 g / 10 min, more preferably 80 g / 10 min or less, further preferably 70 g / 10 min or less, preferably 5 g / 10 min or more, more preferably 10 g / 10 min or more. By making the melt flow rate of the fluororesin within the above range, a fluororesin layer can be easily formed, and the obtained fluororesin layer has excellent mechanical strength.

[0051] In the present disclosure, the melt flow rate of the fluororesin is a value obtained as the mass (g / 10 minutes) of the polymer flowing out from a nozzle having an inner diameter of 2.1 mm and a length of 8 mm at 372°C and a load of 5 kg per 10 minutes using a melt flow indexer (manufactured by Yasuda Seiki Co., Ltd.) in accordance with ASTM D1238.

[0052] The melting point of the fluororesin is preferably 200°C to 322°C, more preferably 220°C or higher, further preferably 240°C or higher, further preferably 260°C or higher, particularly preferably 280°C or higher, and more preferably 320°C or lower.

[0053] The melting point can be determined using a differential scanning calorimeter [DSC].

[0054] Examples of melt-processable fluororesins include tetrafluoroethylene (TFE) / fluoroalkyl vinyl ether (FAVE) copolymers, tetrafluoroethylene (TFE) / hexafluoropropylene (HFP) copolymers, TFE / ethylene copolymers [ETFE], TFE / ethylene / HFP copolymers, ethylene / chlorotrifluoroethylene (CTFE) copolymers [ECTFE], polychlorotrifluoroethylene ethylene [PCTFE], CTFE / TFE copolymers, polyvinylidene fluoride [PVdF], TFE / vinylidene fluoride (VdF) copolymers [VT], polyvinyl fluoride [PVF], TFE / VdF / CTFE copolymers [VTC], and TFE / HFP / VdF copolymers.

[0055] The fluororesin is preferably at least one selected from the group consisting of TFE / FAVE copolymers and TFE / HFP copolymers.

[0056] The fluororesin is preferably at least one selected from the group consisting of TFE / FAVE copolymers and TFE / HFP copolymers, from the viewpoints of excellent heat resistance, moldability, and electrical properties, and stronger adhesion between the conductor and the fluororesin layer.

[0057] TFE / FAVE copolymer is a copolymer containing tetrafluoroethylene (TFE) units and fluoroalkyl vinyl ether (FAVE) units.

[0058] Examples of FAVE constituting the FAVE unit include those selected from the group consisting of the following general formula (1):

[0059] CF2=CFO(CF2CFY 1 O) p -(CF2CF2CF2O) q -Rf (1)

[0060] (In the formula, Y 1represents F or CF3, Rf represents a perfluoroalkyl group having 1 to 5 carbon atoms, p represents an integer of 0 to 5, and q represents an integer of 0 to 5. ) and the general formula (2):

[0061] CFX=CXOCF2OR 1 (2)

[0062] (wherein, X is the same or different and represents H, F or CF3, R 1 It represents a linear or branched fluoroalkyl group having 1 to 6 carbon atoms which may contain 1 to 2 atoms of at least one kind selected from the group consisting of H, Cl, Br and I, or a cyclic fluoroalkyl group having 5 or 6 carbon atoms which may contain 1 to 2 atoms of at least one kind selected from the group consisting of H, Cl, Br and I. At least one of the group consisting of monomers represented by ).

[0063] As FAVE, the monomer represented by the general formula (1) is preferred, more preferably at least one selected from the group consisting of perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether) (PEVE) and perfluoro(propyl vinyl ether) (PPVE), further preferably at least one selected from the group consisting of PEVE and PPVE, and particularly preferably PPVE.

[0064] From the perspective of more firmly adhering the conductor to the fluororesin layer, the content of the FAVE unit in the TFE / FAVE copolymer is preferably 1.0 mol% to 30.0 mol% relative to all monomer units, more preferably 1.2 mol% or more, further preferably 1.4 mol% or more, further preferably 1.6 mol% or more, particularly preferably 1.8 mol% or more, more preferably 3.5 mol% or less, further preferably 3.2 mol% or less, further preferably 2.9 mol% or less, and particularly preferably 2.6 mol% or less.

[0065] From the perspective of more firmly adhering the conductor to the fluororesin layer, the content of the TFE unit in the TFE / FAVE copolymer is preferably 99.0% by mass to 70.0% by mass relative to all monomer units, more preferably 96.5% by mass or more, further preferably 96.8% by mass or more, further preferably 97.1% by mass or more, particularly preferably 97.4% by mass or more, more preferably 98.8% by mass or less, further preferably 98.6% by mass or less, further preferably 98.4% by mass or less, and particularly preferably 98.2% by mass or less.

[0066] In the present disclosure, the content of each monomer unit in the copolymer is expressed by 19 Determined by F-NMR method.

[0067] The TFE / FAVE copolymer may contain monomer units from monomers copolymerizable with TFE and FAVE. In this case, the content of the monomers copolymerizable with TFE and FAVE is preferably 0 to 29.0 mol%, more preferably 0.1 mol% to 5.0 mol%, and further preferably 0.1 mol% to 1.0 mol%, relative to all monomer units of the TFE / FAVE copolymer.

[0068] Examples of monomers copolymerizable with TFE and FAVE include HFP, CZ 1 Z 2 =CZ 3 (CF2) n Z 4 (Where Z 1 , Z 2 and Z 3 Same or different, means H or F, Z 4 represents H, F or Cl, n represents an integer of 2 to 10) and CF2=CF-OCH2-Rf 1 (Where Rf 1 An alkyl perfluorovinyl ether derivative represented by (represents a perfluoroalkyl group having 1 to 5 carbon atoms), a monomer having a functional group, etc. Among them, HFP is preferred.

[0069] The TFE / FAVE copolymer is preferably at least one selected from the group consisting of a copolymer consisting only of a TFE unit and a FAVE unit and the above-mentioned TFE / HFP / FAVE copolymer, and more preferably a copolymer consisting only of a TFE unit and a FAVE unit.

[0070] From the viewpoint of heat resistance and stress crack resistance, the melting point of the TFE / FAVE copolymer is preferably 240° C. to 322° C., more preferably 285° C. or higher, more preferably 320° C. or lower, further preferably 315° C. or lower, particularly preferably 310° C. or lower. The melting point can be measured using a differential scanning calorimeter [DSC].

[0071] The glass transition temperature (Tg) of the TFE / FAVE copolymer is preferably 70° C. to 110° C., more preferably 80° C. or higher, and more preferably 100° C. or lower. The glass transition temperature can be measured by dynamic viscoelasticity measurement.

[0072] From the aspect of electrical properties, the relative dielectric constant of the TFE / FAVE copolymer is preferably 2.4 or less, more preferably 2.1 or less, and the lower limit is not particularly limited, but preferably 1.8 or more. The relative dielectric constant is a value obtained by measuring the changes in the resonant frequency and the electric field strength at a temperature of 20°C to 25°C using a network analyzer HP8510C (manufactured by Hewlett-Packard) and a cavity resonator.

[0073] TFE / HFP copolymer is a copolymer containing tetrafluoroethylene (TFE) units and hexafluoropropylene (HFP) units.

[0074] From the viewpoint of more firmly adhering the conductor to the fluororesin layer, the content of the HFP unit in the TFE / HFP copolymer is preferably 0.1 mol% to 30.0 mol% based on all monomer units, more preferably 0.7 mol% or more, further preferably 1.4 mol% or more, and more preferably 10 mol% or less.

[0075] From the viewpoint of more firmly adhering the conductor to the fluororesin layer, the content of the TFE unit in the TFE / HFP copolymer is preferably 70.0 mol% to 99.9 mol% based on all monomer units, more preferably 90.0 mol% or more, more preferably 99.3 mol% or less, and further preferably 98.6 mol%.

[0076] The TFE / HFP copolymer may also contain monomer units derived from monomers copolymerizable with TFE and HFP. In this case, the content of the monomers copolymerizable with TFE and HFP is preferably 0 to 29.9 mol%, more preferably 0.1 mol% to 5.0 mol%, and even more preferably 0.1 mol% to 1.0 mol%, relative to all monomer units of the TFE / HFP copolymer.

[0077] Examples of monomers copolymerizable with TFE and HFP include FAVE, CZ 1 Z 2 =CZ 3 (CF2) n Z 4 (Where Z 1 , Z 2 and Z 3 Same or different, means H or F, Z 4 represents H, F or Cl, n represents an integer of 2 to 10) and CF2=CF-OCH2-Rf 1 (Where Rf 1 represents a perfluoroalkyl group having 1 to 5 carbon atoms), an alkyl perfluorovinyl ether derivative represented by (represents a perfluoroalkyl group having 1 to 5 carbon atoms), a monomer having a functional group, etc. Among them, FAVE is preferred.

[0078] The melting point of the TFE / HFP copolymer is preferably 200°C to 322°C, more preferably 210°C or higher, further preferably 220°C or higher, particularly preferably 240°C or higher, more preferably 320°C or lower, further preferably less than 300°C, particularly preferably 280°C or lower.

[0079] The glass transition temperature (Tg) of the TFE / HFP copolymer is preferably 60°C to 110°C, more preferably 65°C or higher, and more preferably 100°C or lower.

[0080] The fluororesin preferably has a functional group. When the fluororesin has a functional group, the conductor and the fluororesin layer can be more firmly adhered to each other.

[0081] The functional group is preferably at least one selected from the group consisting of a carbonyl-containing group, an amino group, a hydroxyl group, a difluoromethyl group (—CF 2 H group), an olefin group, an epoxy group, and an isocyanate group.

[0082] The carbonyl-containing group is a group containing a carbonyl group (-C(=O)-) in its structure. Examples of the carbonyl-containing group include:

[0083] Carbonate group [-OC(=O)-OR 3 (Where R 3 is an alkyl group having 1 to 20 carbon atoms or an alkyl group having 2 to 20 carbon atoms containing an ethereal oxygen atom)],

[0084] Acyl [-C(=O)-R 3 (Where R 3 is an alkyl group having 1 to 20 carbon atoms or an alkyl group having 2 to 20 carbon atoms containing an ethereal oxygen atom)],

[0085] Haloformyl [-C(=O)X 5 , X 5 is a halogen atom],

[0086] Formyl [-C(=O)H],

[0087] Formula: -R 4 -C(=O)-R 5 (Where R 4 is a divalent organic group having 1 to 20 carbon atoms, R 5 is a monovalent organic group having 1 to 20 carbon atoms),

[0088] Formula: -OC(=O)-R 6 (Where R 6 is an alkyl group having 1 to 20 carbon atoms or an alkyl group having 2 to 20 carbon atoms containing an ethereal oxygen atom,

[0089] Carboxyl [-C(=O)OH],

[0090] Alkoxycarbonyl [-C(=O)OR 7 (Where R 7 is a monovalent organic group having 1 to 20 carbon atoms)],

[0091] Carbamoyl [-C(=O)NR 8 R 9 (Where R 8 and R 9 may be the same or different and are a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms)],

[0092] Anhydride bond [—C(═O)—OC(═O)—] and the like.

[0093] As R 3 Specific examples of R include methyl, ethyl, propyl, isopropyl, butyl, etc. 4 Specific examples of R include methylene, -CF2-, -C6H4-, etc. 5 Specific examples of R include methyl, ethyl, propyl, isopropyl, and butyl. 7 Specific examples of R include methyl, ethyl, propyl, isopropyl, butyl, etc. 8 and R 9 Specific examples of include a hydrogen atom, a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, and a phenyl group.

[0094] The hydroxyl group is a group represented by -OH or a group including a group represented by -OH. In the present disclosure, -OH constituting a carboxyl group is not included in the hydroxyl group. Examples of the hydroxyl group include -OH, hydroxymethyl, and hydroxyethyl.

[0095] An olefin group is a group having a carbon-carbon double bond. Examples of the olefin group include the following formulas:

[0096] -CR 10 =CR 11 R 12

[0097] (Where R 10 , R 11 and R 12 The functional group may be the same or different and is represented by a hydrogen atom, a fluorine atom or a monovalent organic group having 1 to 20 carbon atoms, and is preferably at least one selected from the group consisting of -CF=CF2, -CH=CF2, -CF=CHF, -CF=CH2 and -CH=CH2.

[0098] The isocyanate group is a group represented by -N=C=O.

[0099] From the viewpoint of more firmly adhering the conductor to the fluororesin layer, the number of functional groups of the fluororesin is 6 The number of carbon atoms is preferably 5 to 1300. 6The number of functional groups is more preferably 50 or more, further preferably 100 or more, particularly preferably 200 or more, more preferably 1000 or less, further preferably 800 or less, particularly preferably 700 or less, and most preferably 500 or less.

[0100] In addition, since a coating layer with excellent electrical properties can be formed, the number of functional groups of the fluororesin per 10 6 The number of carbon atoms may be less than 5.

[0101] The functional groups are functional groups present at the main chain end or side chain end of the copolymer (fluororesin), and functional groups present in the main chain or side chain, preferably present at the main chain end. Examples of the functional groups include -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2, -CH2OH, etc., preferably at least one selected from the group consisting of -CF2H, -COF, -COOH, -COOCH3 and -CH2OH. -COOH includes a dicarboxylic anhydride group (-CO-O-CO-) formed by two -COOH bonds.

[0102] The identification of the types of the functional groups and the measurement of the number of the functional groups can be performed using infrared spectroscopy.

[0103] The number of functional groups is specifically determined by the following method. First, the copolymer is melted at 330°C to 340°C for 30 minutes and compression molded to produce a film with a thickness of 0.20 mm to 0.25 mm. The film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the copolymer, and a differential spectrum is obtained from the background spectrum in which the functional groups are completely fluorinated and do not exist. According to the following formula (A), the number of functional groups per 1×10 6 The number of functional groups N per carbon atom.

[0104] N=I×K / t(A)

[0105] I: Absorbance

[0106] K: Correction coefficient

[0107] t: film thickness (mm)

[0108] For reference, regarding the functional groups in the present disclosure, the absorption frequency, molar absorption coefficient, and correction coefficient are shown in Table 1. The molar absorption coefficient was determined from FT-IR measurement data of a low-molecular model compound.

[0109] [Table 1]

[0110] Table 1

[0111]

[0112] It should be noted that the absorption frequencies of -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, and -CH2CONH2 are several tens of kaise (cm-1) lower than the absorption frequencies of -CF2H, -COF, free -COOH, and bonded -COOH, -COOCH3, and -CONH2 shown in the table, respectively. 1 ).

[0113] Thus, for example, the functional group number of -COF refers to the absorption frequency 1883 cm-1 due to -CF2COF. 1 The number of functional groups obtained from the absorption peak at 1840 cm-1 due to -CH2COF 1 The total number of functional groups found from the absorption peak at .

[0114] The above-mentioned number of functional groups can be the total number of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2 and -CH2OH, or the total number of -CF2H, -COF, -COOH, -COOCH3 and -CH2OH.

[0115] The functional groups are introduced into the fluororesin (copolymer) by, for example, a chain transfer agent or a polymerization initiator used when manufacturing the fluororesin. For example, when an alcohol is used as a chain transfer agent or a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced into the main chain end of the fluororesin. In addition, by polymerizing a monomer having a functional group, the functional group is introduced into the side chain end of the fluororesin. The fluororesin may contain units derived from a monomer having a functional group.

[0116] Examples of monomers having a functional group include cyclic hydrocarbon monomers having a dicarboxylic anhydride group (-CO-O-CO-) and a polymerizable unsaturated group in the ring as described in Japanese Patent Application Laid-Open No. 2006-152234, and monomers having a functional group (f) as described in International Publication No. 2017 / 122743. Examples of monomers having a functional group include monomers having a carboxyl group (maleic acid, itaconic acid, citraconic acid, undecylenic acid, etc.); monomers having an anhydride group (itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, maleic anhydride, etc.), and monomers having a hydroxyl group or an epoxy group (hydroxybutyl vinyl ether, glycidyl vinyl ether, etc.).

[0117] The fluororesin can be produced, for example, by appropriately mixing monomers that will serve as structural units thereof and additives such as a polymerization initiator and subjecting them to conventionally known methods such as emulsion polymerization and suspension polymerization.

[0118] The fluororesin layer may contain other components as required. As other components, crosslinking agents, antistatic agents, heat stabilizers, foaming agents, foaming nucleating agents, antioxidants, surfactants, photopolymerization initiators, anti-wear agents, surface modifiers, pigments and other additives may be cited. The content of other components in the fluororesin layer is preferably less than 1% by mass, more preferably less than 0.5% by mass, and further preferably less than 0.1% by mass relative to the mass of the fluororesin in the fluororesin layer. The lower limit is not particularly limited and may be more than 0% by mass. That is, the fluororesin layer may not contain other components.

[0119] From the viewpoint of insulation properties, the thickness of the fluororesin layer is preferably 10 μm to 295 μm, more preferably 20 μm or more, further preferably 30 μm or more, more preferably 270 μm or less, further preferably 250 μm or less.

[0120] The relative dielectric constant of the fluororesin layer is preferably 2.5 or less, more preferably 2.4 or less, further preferably 2.3 or less, further preferably 2.2 or less, particularly preferably 2.1 or less, and preferably 1.8 or more. The relative dielectric constant is a value obtained by measuring changes in resonance frequency and electric field intensity at a temperature of 20°C to 25°C using a network analyzer HP8510C (manufactured by Hewlett-Packard) and a cavity resonator.

[0121] (PAEK resin layer)

[0122] The PAEK resin layer is formed around the fluororesin layer and contains a polyaryletherketone (PAEK) resin. The PAEK resin layer can constitute the outermost layer of the insulated wire. By constituting the outermost layer with the PAEK resin layer, an insulated wire having a coating layer that is not easily damaged when inserted into a slot of an iron core of a rotating electric machine or when bent in the side direction can be obtained, and that does not repel a varnish used to fix the coated wire to the iron core.

[0123] The PAEK resin is not particularly limited as long as it contains repeating units composed of an arylene group, an ether group [—O—], and a carbonyl group [—C(═O)—]. Examples thereof include resins containing repeating units represented by any of the following formulae (a1) to (a5).

[0124] [-Ar-O-Ar-C(=O)-](a1)

[0125] [-Ar-O-Ar-C(=O)-Ar-C(=O)-](a2)

[0126] [-Ar-O-Ar-O-Ar-C(=O)-](a3)

[0127] [-Ar-O-Ar-C(=O)-Ar-O-Ar-C(=O)-Ar-C(=O)-](a4)

[0128] [-Ar-O-Ar-O-Ar-C(=O)-Ar-C(=O)-](a5)

[0129] (In the formula, Ar represents a divalent aromatic hydrocarbon ring group which may have a substituent.)

[0130] Examples of the divalent aromatic hydrocarbon ring group represented by Ar include phenylene (o-phenylene, m-phenylene, p-phenylene, etc.), arylene groups having 6 to 10 carbon atoms such as naphthylene, biarylene groups (each having 6 to 10 carbon atoms) such as biphenylene (2,2'-biphenylene, 3,3'-biphenylene, 4,4'-biphenylene, etc.), triarylene groups (each having 6 to 10 carbon atoms) such as o-triphenylene, m-triphenylene, p-triphenylene, etc. These aromatic hydrocarbon ring groups may have a substituent, such as a halogen atom, an alkyl group (a linear or branched alkyl group having 1 to 4 carbon atoms such as a methyl group), a haloalkyl group, a hydroxyl group, an alkoxy group (a linear or branched alkoxy group having 1 to 4 carbon atoms such as a methoxy group), a mercapto group, an alkylthio group, a carboxyl group, a sulfo group, an amino group, an N-substituted amino group, a cyano group, etc. In the repeating units (a1) to (a5), the types of Ar may be the same or different from each other. Preferred Ar is phenylene (eg, p-phenylene) or biphenylene (eg, 4,4'-biphenylene).

[0131] As the resin having repeating unit (a1), polyetherketone (for example, "PEEK-HT" manufactured by Victrex) and the like can be exemplified. As the resin having repeating unit (a2), polyetherketoneketone (for example, "PEKK" manufactured by Arkema + Oxford Performance Material) and the like can be exemplified. As the resin having repeating unit (a3), polyetheretherketone (for example, "VICTREX PEEK" manufactured by Victrex, "Vestakeep (registered trademark)" manufactured by Evonik, "Vestakeep-J" manufactured by Daicel Evonik, "KetaSpire (registered trademark)" manufactured by Solvay Speciality Polymers) and polydiphenylether-phenylether-phenylketone (for example, "Kadel (registered trademark)" manufactured by Solvay Speciality Polymers) and the like can be exemplified. As the resin having repeating unit (a4), polyetherketoneetherketoneketone (for example, "VICTREX ST" manufactured by Victrex) and the like can be exemplified. Examples of the resin having a repeating unit (a5) include polyetheretherketoneketone and the like.

[0132] In the repeating unit composed of an arylene group, an ether group and a carbonyl group, the ratio of the ether segment (E) to the ketone segment (K) is, for example, E / K=0.5 to 3, preferably about 1 to 2.5. The ether segment imparts flexibility to the molecular chain, and the ketone segment imparts rigidity to the molecular chain. Therefore, the more ether segments there are, the faster the crystallization speed is, and the higher the crystallinity that can be finally achieved is. The more ketone segments there are, the higher the glass transition temperature and melting point tend to be. These PAEK resins can be used alone or in combination of two or more.

[0133] Among these PAEK resins, a resin having any one of the repeating units (a1) to (a3) ​​is preferred. For example, the PAEK resin is preferably at least one resin selected from the group consisting of polyetherketone, polyetheretherketone, polyetherketoneketone, and polyetherketoneetherketoneketone.

[0134] In particular, from the viewpoint of an excellent balance between the height of the glass transition temperature and the melting point and the speed of crystallization, a PAEK resin having a repeating unit (a3) ​​is more preferred, and polyetheretherketone is particularly preferred.

[0135] PAEK resin in 60 seconds -1 The melt viscosity at 390°C is preferably 0.01 kNsm -2 ~4.0kNsm -2 The preferred lower limit of melt viscosity is 0.05 kNsm -2 , more preferably 0.10 kNsm -2 , more preferably 0.15 kNsm -2 The preferred upper limit of melt viscosity is 2.5 kNsm -2 , more preferably 1.5 kNsm -2 , more preferably 1.0 kNsm -2 , particularly preferably 0.5 kNsm -2 , most preferably 0.4kNsm -2 The melt viscosity of PAEK resin is measured according to ASTM D3835.

[0136] The glass transition temperature of the PAEK resin is preferably 130° C. or higher, more preferably 135° C. or higher, and further preferably 140° C. or higher. The glass transition temperature is measured using a differential scanning calorimetry (DSC) apparatus.

[0137] The melting point of the PAEK resin is preferably 300° C. or higher, more preferably 320° C. or higher. The melting point is measured using a differential scanning calorimeter (DSC).

[0138] From the viewpoint of insulation properties, the thickness of the PAEK resin layer is preferably 5 μm to 100 μm, more preferably 10 μm or more, further preferably 15 μm or more, more preferably 80 μm or less, further preferably 70 μm or less.

[0139] (Composite resin layer)

[0140] The covering layer of the covered electric wire preferably further comprises a composite resin layer formed between the fluororesin layer and the PAEK resin layer. By further comprising the composite resin layer on the covering layer, the fluororesin layer and the PAEK resin layer can be firmly adhered to each other via the composite resin layer.

[0141] The composite resin layer contains melt-processable fluororesin and PAEK resin.

[0142] As the fluororesin included in the composite resin layer, the same fluororesin as the fluororesin included in the fluororesin layer can be cited, preferably the same fluororesin as the fluororesin included in the fluororesin layer. In addition, if the composite resin layer is composed of the same fluororesin as the fluororesin included in the fluororesin layer, the adhesion between the fluororesin layer and the composite resin layer can be further improved. For example, the fluororesin included in the fluororesin layer and the composite resin layer can be a copolymer containing TFE units and FAVE units.

[0143] The fluororesin contained in the composite resin layer also preferably has functional groups similar to those of the fluororesin contained in the fluororesin layer. The suitable number of functional groups of the fluororesin contained in the fluororesin layer is also the same as that of the fluororesin contained in the fluororesin layer.

[0144] As the PAEK resin contained in the composite resin layer, the same PAEK resin as the PAEK resin contained in the PAEK resin layer can be cited, preferably the same PAEK resin as the PAEK resin contained in the PAEK resin layer. In addition, if the composite resin layer is composed of the same PAEK resin as the PAEK resin contained in the PAEK resin layer, the adhesion between the composite resin layer and the PAEK resin layer can be further improved. For example, the PAEK resin contained in the composite resin layer and the PAEK resin layer can be polyetheretherketone.

[0145] The adhesion between the fluororesin layer and the composite resin layer is preferably 0.1 N / mm or more, more preferably 0.2 N / mm or more, further preferably 0.3 N / mm or more, particularly preferably 0.4 N / mm or more.

[0146] The adhesion between the composite resin layer and the PAEK resin layer is preferably 0.1 N / mm or more, more preferably 0.2 N / mm or more, further preferably 0.3 N / mm or more, and particularly preferably 0.4 N / mm or more.

[0147] From the viewpoint of insulation properties and adhesion, the thickness of the composite resin layer is preferably 5 μm to 50 μm, more preferably 10 μm or more, further preferably 15 μm or more, more preferably 40 μm or less, further preferably 30 μm or less.

[0148] (Manufacturing method of insulated electric wire)

[0149] The insulated wire of the present disclosure can be produced, for example, by the following production method.

[0150] (1) A manufacturing method in which a fluororesin is heated by an extruder to melt the fluororesin, the molten fluororesin is extruded onto a conductor to form a fluororesin layer, and then a molten PAEK resin is extruded onto the fluororesin layer to form a PAEK resin layer;

[0151] (2) A method for forming a PAEK resin layer by heating a fluororesin using an extruder to melt the fluororesin, extruding the molten fluororesin onto a conductor to form a fluororesin layer, and simultaneously extruding a molten PAEK resin onto the fluororesin layer;

[0152] (3) A manufacturing method in which a fluororesin is heated using an extruder to melt the fluororesin, the molten fluororesin is extruded onto a conductor to form a fluororesin layer, and then a heat shrinkable tube containing a PAEK resin is covered and the heat shrinkable tube is shrunk to form a PAEK resin layer; etc.

[0153] In the manufacturing methods (1) to (3), by extruding the molten fluororesin onto a conductor heated to a temperature higher than the temperature of the molten fluororesin, a covered electric wire in which the conductor and the fluororesin layer are closely bonded with sufficient strength can be obtained. Since the insulated electric wire obtained by such a manufacturing method is closely bonded with the conductor and the coating layer (fluororesin layer) with high strength, even if the insulated electric wire is bent, the coating layer is unlikely to float from the conductor, and wrinkles are unlikely to occur in the coating layer.

[0154] The extrusion molding machine is not particularly limited, and an extrusion molding machine including a barrel, a die head, and a pipe joint having a through port for feeding out a conductor can be used.

[0155] The temperature of the fluororesin in a molten state is usually above the melting point of the fluororesin, preferably a temperature 15°C higher than the melting point of the fluororesin, more preferably a temperature 20°C higher than the melting point of the fluororesin, and further preferably a temperature 25°C higher than the melting point of the fluororesin. There is no upper limit to the temperature of the fluororesin in a molten state, for example, it may be less than the thermal decomposition temperature of the fluororesin. The temperature of the fluororesin in a molten state can be adjusted by adjusting the temperature of the barrel of the extruder, the temperature of the die, etc. The temperature of the fluororesin in a molten state can be determined, for example, by measuring the temperature of the fluororesin discharged from the die outlet using a thermocouple.

[0156] The temperature of the conductor after heating is higher than the temperature of the fluororesin in a molten state, preferably 15° C. or higher, more preferably 20° C. or higher. The upper limit of the temperature of the conductor after heating is not limited, and is, for example, 700° C. or lower. The temperature of the conductor after heating can be determined, for example, by measuring the temperature of the conductor between the heating device and the extruder using a contact thermometer or a non-contact thermometer.

[0157] The temperature of the heated conductor can be adjusted by heating the conductor before feeding it into the extruder using a heating device. As a heating device, any device that heats a certain range at once at high temperature, such as a halogen heater, a carbon heater, a tungsten heater, a hot air heating device, an induction heating device, a microwave heating device, a superheated steam generating device, a burner, etc., can be used. The size, shape, number of devices, and number of heating sources are not limited. In addition, different methods can be used in combination with each other, and multiple heat sources can be used. For the reason that a large range can be irradiated uniformly at once, it is preferred to use a halogen heater for heating.

[0158] The heating conditions are not particularly limited as long as the conductor temperature when the conductor contacts the resin is higher than the molding temperature (head temperature), and the distance between the molding machine and the heating device can be close or far. In addition, different heating devices, heating pipes, insulation pipes, and insulation materials can be provided around the running line after passing through the conductor heating range for the purpose of heat preservation of the conductor.

[0159] The line speed during extrusion molding may be 0.1 m / min to 50 m / min, and is preferably 20 m / min or less.

[0160] After forming the fluororesin layer, the insulated wire may be cooled. The cooling method is not particularly limited, and may be water cooling, air cooling, or the like. When the insulated wire is cooled by air cooling, it can be cooled at a moderate speed, so there is a tendency for the thickness of the coating layer to become uniform.

[0161] After forming the coating layer, the insulated wire may be subjected to heat treatment. The heat treatment may be performed before or after cooling the insulated wire. By performing the heat treatment, the adhesion between the conductor and the fluororesin layer can be further improved.

[0162] The heat treatment can be performed by heating the insulated wire in batches or continuously using a hot air circulation furnace or a heating furnace using high frequency induction heating. Alternatively, it can be performed by a salt bath method. In the salt bath method, the resin coated conductor is heated by passing it through a molten salt. Examples of the molten salt include a mixture of potassium nitrate and sodium nitrate.

[0163] The temperature of the heat treatment is usually not less than the glass transition temperature of the fluororesin, preferably not less than 15° C. higher than the melting point, and preferably not more than 50° C. higher than the melting point of the fluororesin.

[0164] From the perspective of further improving the adhesion between the conductor and the fluororesin layer and suppressing oxidation of the conductor, the heat treatment time is preferably 0.1 to 15 minutes, more preferably 0.5 minutes or more, and more preferably 10 minutes or less. If heated at high temperature for a long time, the copper core wire may be oxidized and discolored.

[0165] The insulated electric wire of the present disclosure may be suitably used as an industrial motor winding or a flat magnet wire.

[0166] The insulated wire of the present invention can be wound and used as a coil. The insulated wire and coil of the present invention can be suitably used in electric devices or electronic devices such as motors, generators, and inductors. In addition, the insulated wire and coil of the present invention can be suitably used in electric devices or electronic devices such as vehicle-mounted motors, vehicle-mounted generators, and vehicle-mounted inductors.

[0167] Although the embodiments have been described above, it should be understood that various changes in the embodiments and details may be made without departing from the spirit and scope of the claims.

[0168] <1> According to a first aspect of the present disclosure, there is provided an insulated wire comprising a conductor and a covering layer formed around the conductor, wherein the covering layer comprises: a fluororesin layer containing a melt-processable fluororesin; and a PAEK resin layer formed around the fluororesin layer and containing a polyaryletherketone (PAEK) resin, wherein the thickness of the covering layer is 40 μm to 300 μm.

[0169] <2> According to a second aspect of the present disclosure, there is provided the insulated wire according to the first aspect, wherein a ratio of the mass of the fluororesin layer to the mass of the insulated wire is 50% by mass or more.

[0170] <3> According to a third aspect of the present disclosure, there is provided the insulated wire according to the first aspect or the second aspect, wherein the coating layer has a relative dielectric constant of 2.9 or less.

[0171] <4> According to a fourth aspect of the present disclosure, there is provided an insulated wire according to any one of the first to third aspects, wherein a partial discharge inception voltage measured at 25° C. satisfies the following relational expression.

[0172] Partial discharge inception voltage (V) ≥ 2.2 × X + 810

[0173] X: Ratio of the mass of the fluororesin layer to the mass of the insulated wire (mass %)

[0174] <5> According to a fifth aspect of the present disclosure, there is provided an insulated wire according to any one of the first to fourth aspects, wherein a rate of change calculated by the following formula is less than 10%.

[0175] Change rate (%) = [(partial discharge inception voltage measured at 25°C) - (partial discharge inception voltage measured at 200°C)] / (partial discharge inception voltage measured at 25°C) × 100

[0176] <6> According to a sixth aspect of the present disclosure, there is provided an insulated wire according to any one of the first to fifth aspects, wherein a rate of change calculated from the following formula is less than 10%.

[0177] Change rate (%) = [(partial discharge inception voltage measured at 25°C after heating the insulated wire at 200°C for 1000 hours) - (partial discharge inception voltage measured at 25°C)] / (partial discharge inception voltage measured at 25°C) × 100

[0178] <7> According to a seventh aspect of the present disclosure, there is provided an insulated wire according to any one of the first to sixth aspects, wherein the thickness of the PAEK resin layer is 15 μm or more,

[0179] The load required for power on is 1500g or more.

[0180] <8> According to an eighth aspect of the present disclosure, there is provided the insulated wire according to any one of the first to seventh aspects, wherein the fluororesin contained in the fluororesin layer has a melt flow rate of 0.1 g / 10 min to 120 g / 10 min.

[0181] <9> According to a ninth aspect of the present disclosure, there is provided the insulated wire according to any one of the first to eighth aspects, wherein the fluororesin contained in the fluororesin layer has a melting point of 240°C to 320°C.

[0182] <10> According to a tenth aspect of the present disclosure, there is provided the insulated wire according to any one of the first to ninth aspects, wherein the fluororesin contained in the fluororesin layer contains a tetrafluoroethylene unit and a fluoroalkyl vinyl ether unit.

[0183] <11> According to an eleventh aspect of the present disclosure, there is provided an insulated wire according to any one of the first to tenth aspects, wherein the content of the fluoroalkyl vinyl ether unit of the fluororesin contained in the fluororesin layer is 1.0 mol % to 30.0 mol % based on all monomer units.

[0184] <12> According to a twelfth aspect of the present disclosure, there is provided the insulated wire according to any one of the first to ninth aspects, wherein the fluororesin contained in the fluororesin layer contains a tetrafluoroethylene unit and a hexafluoropropylene unit.

[0185] <13> According to a 13th aspect of the present disclosure, there is provided an insulated wire according to any one of the 1st to 12th aspects, wherein the fluororesin contained in the fluororesin layer has a functional group, and the number of the functional groups of the fluororesin is 1:1 per 10 6 The number of carbon atoms ranges from 5 to 1300.

[0186] <14> According to a fourteenth aspect of the present disclosure, there is provided an insulated wire according to any one of the first to thirteenth aspects, wherein the fluororesin has at least one functional group selected from the group consisting of a carbonyl-containing group, an amino group, a hydroxyl group, a difluoromethyl group, an olefin group, an epoxy group, and an isocyanate group.

[0187] <15> According to a fifteenth aspect of the present disclosure, there is provided the insulated wire according to any one of the first to fourteenth aspects, wherein the conductor is made of at least one selected from the group consisting of copper, copper alloys, aluminum, and aluminum alloys.

[0188] <16> According to a sixteenth aspect of the present disclosure, there is provided an insulated wire according to any one of the first to fifteenth aspects, wherein a cross-sectional shape of the conductor is any one of a circle, an ellipse, a rectangle, a square, and a polygon.

[0189] <17> According to the 17th aspect of the present disclosure, there is provided an insulated wire based on any one of the 1st to 16th aspects, wherein the covering layer further comprises a composite resin layer, the composite resin layer is formed between the fluororesin layer and the PAEK resin layer, and contains a melt-processable fluororesin and a PAEK resin, and the adhesion between the fluororesin layer and the composite resin layer, and the adhesion between the composite resin layer and the PAEK resin layer are both 0.1 N / mm or more.

[0190] <18> According to an eighteenth aspect of the present disclosure, there is provided the insulated wire according to any one of the first to seventeenth aspects, wherein the fluororesin contained in the composite resin layer contains a tetrafluoroethylene unit and a fluoroalkyl vinyl ether unit.

[0191] <19> According to a 19th aspect of the present disclosure, there is provided an insulated wire according to the 17th aspect or the 18th aspect, wherein the fluororesin contained in the composite resin layer has a functional group, and the number of the functional groups of the fluororesin is 10 6 The number of carbon atoms ranges from 5 to 1300.

[0192] <20> According to a 20th aspect of the present disclosure, there is provided an insulated wire according to any one of the first to nineteenth aspects, which is an industrial motor winding or a flat magnet wire.

[0193] Example

[0194] Next, embodiments of the present disclosure will be described with reference to examples, but the present disclosure is not limited to the above examples.

[0195] Each numerical value in the examples was measured by the following method.

[0196] (Melt Flow Rate (MFR))

[0197] According to ASTM D1238, the mass (g / 10 minutes) of the copolymer flowing out from a nozzle having an inner diameter of 2.1 mm and a length of 8 mm at 372°C and a load of 5 kg per 10 minutes was determined using a melt flow indexer (manufactured by Yasuda Seiki Co., Ltd.).

[0198] (Melting Point)

[0199] The temperature was determined as the temperature corresponding to the maximum value of the heat of fusion in the heat of fusion curve when the temperature was increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].

[0200] (Composition of fluororesin)

[0201] pass 19 The measurement was carried out by F-NMR method.

[0202] (Coating thickness)

[0203] One end of the insulated wire was cut off by 10 mm to obtain a wire sample, which was hardened with a hardener and the cross section was polished.

[0204] The cross section of the sample was magnified 50 times using a video microscope (Keyence VHX-S660), and measurements were taken at three locations each on the top, bottom, left and right sides (12 locations in total). The average value was calculated and used as the coating thickness.

[0205] (Relative dielectric constant)

[0206] A film was formed by a co-extruder in a manner to form the wire coating structure of the embodiment or the comparative example. The obtained film was cut into strips with a width of 2 mm and a length of 100 mm, and the relative dielectric constant was measured under the conditions of 1 MH and 20°C to 25°C by a cavity resonator perturbation method (dielectric constant measuring device manufactured by Kanto Electronics Application Development Co., Ltd., network analyzer manufactured by Agilent Technologies Co., Ltd.).

[0207] (Partial Discharge Inception Voltage (PDIV) (25℃, 200℃))

[0208] Two insulated wires were cut into 90 cm lengths, twisted while applying a tension of 13.5 N, and twisted coils with 8 twists in the range of 125 mm in the center were made. Then, the insulating film of 10 mm at the end of the sample was removed, and a partial discharge measuring device (DAC-PD-7 manufactured by Soken Electric Co., Ltd.) was used to apply a 50 Hz sine wave AC voltage between the conductors of the two insulated wires at an ambient temperature of 25°C (relative humidity 50%) or an ambient temperature of 200°C (relative humidity 50%), thereby measuring. The voltage rise rate was set to 50 V / sec, the voltage drop rate was set to 50 V / sec, the voltage holding time was set to 0 sec, and the voltage at the moment when a discharge of 10 pC or more was generated was taken as the partial discharge starting voltage.

[0209] In addition, the change rate (%) was calculated according to the following formula.

[0210] Change rate (%) = [(PDIV measured at 25°C) - (PDIV measured at 200°C)] / (PDIV measured at 25°C) × 100

[0211] (Long-term durability test (200℃×1000H PDIV))

[0212] Cut two insulated wires with a length of 90 cm, twist them while applying a tension of 13.5 N, and make a twisted coil with 8 twisted parts in the range of 125 mm in the central part. Then, remove the insulating film of 10 mm at the end of the sample, and expose the sample in an electric furnace at 200°C for 1000H (1000 hours). Cool the exposed sample at room temperature for 24 hours, and use a partial discharge measuring device (DAC-PD-7 made by Soken Electric Co., Ltd.) to apply a 50Hz sinusoidal AC voltage between the conductors of the two insulated wires for measurement. Set the voltage increase rate to 50V / sec, the voltage reduction rate to 50V / sec, and the voltage holding time to 0 seconds. The voltage at the moment when a discharge of 10pC or more is generated is taken as the partial discharge starting voltage.

[0213] In addition, the change rate (%) was calculated according to the following formula.

[0214] Change rate (%) = [(PDIV measured after long-term durability test) - (PDIV measured at 25°C)] / (PDIV measured at 25°C) × 100

[0215] (Abrasion resistance test)

[0216] The unidirectional wear test was conducted using a wear tester No. 215 scratch tester (manufactured by Yasuda Seiki Co., Ltd.). A continuously increasing force was applied to a needle, and the needle was rubbed against the surface of the coating layer of the insulated wire. The force when conduction was established between the needle and the conductor was taken as the destructive force (g).

[0217] Test method: JIS C3216-3

[0218] (Varnish impregnation)

[0219] The surface layer of the insulated wire was coated with varnish using YE-7309 (ATF-resistant varnish / two-component type) manufactured by Ryoden Kasei Co., Ltd.

[0220] ○: Does not reject varnish

[0221] ×: Repel varnish

[0222] (Interlayer adhesion) (Peel strength)

[0223] Use AGS-J Autograph (50N) (manufactured by Shimadzu Corporation) for measurement. Cut two strips of 50 mm approximately parallel in the long axis direction, cut the film at both ends into a right angle along the short axis direction, peel off 10 mm at the end, and clamp it on the upper chuck. The conductor is fixed to the lower part in a horizontal manner in the long face direction. When moving the device in the tensile direction, use a clamp that moves in a linked manner in the transverse direction according to its longitudinal movement distance, and adjust the angle so that the peeled film is always perpendicular to the conductor in the long face direction. Measure the tensile stress when it is stretched at 100 mm / min to peel off 30 mm, and take its maximum point stress as the peel strength.

[0224] That is, the peel strength of the film (coating) on ​​the main surface of the flat conductor of the insulated wire is measured using AGS-J Autograph (50N) (manufactured by Shimadzu Corporation). Here, the surface with the larger dimension in the width direction of the conductor in the two sets of opposing surfaces of the flat conductor (the surface of the long side at right angles to the length direction of the conductor) is set as the main surface, and the surface orthogonal to the main surface (the surface of the short side at right angles to the length direction) is set as the side surface. The dimension in the width direction of the conductor of the main surface is larger than the dimension in the width direction of the conductor of the side surface. Two roughly parallel incisions are formed on the film on one main surface along the length direction of the insulated wire, and then two incisions orthogonal to the length direction are formed at intervals of 50 mm in the length direction. The end of the film with the incision is peeled off from the conductor, and a clamping margin of 10 mm is set. The insulated wire is fixed to the fixture in a manner that the other main surface faces downward, and the clamping margin is clamped in the upper chuck and folded back 90 degrees. A jig was used that moved so that the angle between the insulated wire fixed to the jig and the film was maintained at 90 degrees. The film was peeled off by 30 mm at a tensile speed of 100 mm / min, and the tensile stress was measured. The maximum point stress was taken as the peel strength.

[0225] (Coating damage)

[0226] Insert the wire into the virtual stator to check the coating status.

[0227] 0:No damage to the coating

[0228] ×: The coating is damaged

[0229] Embodiments 1 to 4

[0230] The insulating film forming resin used is a copolymer of tetrafluoroethylene and perfluoro(propyl vinyl ether) (PFA), a resin with an MFR of 14g / 10min and a melting point of 306°C; and a resin with an MFR of 36g / 10min and a melting point of 343°C, polyetherketone (PEEK) (KT-880P manufactured by SOLVAY Co., Ltd.). In the wire structure, PFA is used for the inner insulating layer, PEEK is used for the outer insulating layer, and AC1.0 is used for the conductor. The coating thickness of all layers is unified to 100μm, and the coating thickness of each layer is adjusted so that the weight ratio of PFA is 50Wt% to 90Wt%.

[0231] In addition, the wire forming machine uses The co-extruder set the die temperature at the front end to 390° C. and pulled at a speed of 30 m / min.

[0232] Example 5

[0233] The outer layer of the insulating film forming resin of Example 5 was polyetherketoneetherketoneketone (PEKK) (KEPSTAN7002 manufactured by ARKEMA Co., Ltd.), a resin having an MFR of 35 g / 10 minutes and a melting point of 331°C, and the coating thickness of all layers was set to 100 μm, and the coating thickness of each layer was adjusted so that the weight ratio of PFA was 80 wt%. Insulated wires were molded under the same conditions as Examples 1 to 4 except for the above.

[0234] Embodiment 6-7

[0235] The insulating film forming resins used in Examples 6 to 7 are a copolymer of tetrafluoroethylene and perfluoro(propyl vinyl ether) (PFA), a resin with an MFR of 68 g / 10 minutes and a melting point of 301°C; a copolymer of tetrafluoroethylene and perfluoro(propyl vinyl ether) (PFA), a resin with an MFR of 28 g / 10 minutes and a melting point of 303°C; and a polyetherketone (PEEK) (KT-880P manufactured by SOLVAY), a resin with an MFR of 36 g / 10 minutes and a melting point of 343°C. The coating thickness of all layers was unified to 100 μm, and the coating thickness of each layer was adjusted so that the weight ratio of PFA was 80 wt%. Insulated wires were molded under the same conditions as in Examples 1 to 4 except for the above.

[0236] Embodiments 8 to 9

[0237] In the insulated wires of Examples 8 to 9, the coating thickness of all layers was set to 200 μm and 300 μm, and the coating thickness was adjusted so that the PFA weight ratio was 80 wt%. Insulated wires were molded under the same conditions as in Examples 1 to 4 except for the above.

[0238] Comparative Examples 1 to 3

[0239] The insulating film forming resins of Comparative Examples 1 to 3 are a copolymer of tetrafluoroethylene and perfluoro(propyl vinyl ether) (PFA), a resin with an MFR of 14 g / 10 minutes and a melting point of 306°C; a polyetherketone (PEEK) (KT-880P manufactured by SOLVAY), a resin with an MFR of 36 g / 10 minutes and a melting point of 343°C; and a polyetherketoneetherketoneketone (PEKK) (KEPSTAN7002 manufactured by ARKEMA), a resin with an MFR of 35 g / 10 minutes and a melting point of 331°C, to form a single-layer coated wire. The coating thickness is 100 μm, and the wire forming machine uses The temperature of the die at the front end of the short-shaft extruder was set to 390° C. and the extruder was pulled at a speed of 30 m / min.

[0240] It was confirmed that the PDIV change rate in a 200°C atmosphere and the PDIV change rate in a long-term durability test (200°C×1000H) of Examples 1 to 5 were about 1 / 3 lower than those of Comparative Examples 2 and 3.

[0241] It was confirmed that the outer layer was coated with PAEK resin, and the abrasion resistance was improved by 3 times compared with Comparative Example 1 (PFA single-layer electric wire). Furthermore, it was confirmed that the varnish impregnation was acceptable.

[0242] Example 13

[0243] The insulating film forming resin used is a copolymer of tetrafluoroethylene and perfluoro(propyl vinyl ether) (PFA), a resin with an MFR of 14g / 10min and a melting point of 306°C; and a resin with an MFR of 36g / 10min and a melting point of 343°C, a polyetherketone (PEEK) (KT-880P manufactured by SOLVAY Co., Ltd.). In the wire structure, PFA is used for the inner insulating layer, PEEK is used for the outer insulating layer, and the conductor is a flat conductor with a length of 2.0mm and a width of 3.4mm. The coating thickness of all layers is set to 100μm, and the coating thickness of each layer is adjusted so that the weight ratio of PFA becomes 80Wt%.

[0244] In addition, the wire forming machine uses The co-extruder set the die temperature at the front end to 390° C. and pulled at a speed of 5 m / min.

[0245] Embodiment 14

[0246] An insulated wire was molded under the same conditions as in Example 13 except that polyetherketoneetherketoneketone (PEKK) (KEPSTAN7002 manufactured by ARKEMA) having an MFR of 35 g / 10 min and a melting point of 331° C. was used for the outer layer.

[0247] Comparative Example 4

[0248] The insulating film forming resin used is a copolymer of tetrafluoroethylene and perfluoro(propyl vinyl ether) (PFA), with an MFR of 14g / 10 minutes and a melting point of 306°C. The conductor is a flat conductor with a length of 2.0mm and a width of 3.4mm. The single-layer coated wire is formed with a coating thickness of 100μm. The wire forming machine uses The temperature of the die at the front end of the short-shaft extruder was set to 390° C. and the extruder was pulled at a speed of 5 m / min.

[0249] Embodiment 15, 16

[0250] An insulated wire was produced in the same manner as in Examples 13 and 14, except that a mixture of a copolymer of tetrafluoroethylene and perfluoro(propyl vinyl ether) (PFA) having an MFR of 14 g / 10 min and a melting point of 306°C and polyetherketone (PEEK) (KT-880P manufactured by SOLVAY) having an MFR of 36 g / 10 min and a melting point of 343°C was used to form an adhesive layer between the inner layer and the outer layer.

[0251] It was confirmed that the covered electric wires of Examples 13 to 16 had no covering damage when inserted into the dummy stator. It was also confirmed that the bonding strength of each covering layer was sufficient.

[0252] The above results are shown in Tables 2 and 3.

[0253]

[0254]

Claims

1. An insulated wire comprising a conductor and a coating layer formed around the conductor, wherein: The coating layer comprises: a fluororesin layer containing a melt-processable fluororesin; and a PAEK resin layer formed around the fluororesin layer and containing a polyaryletherketone (PAEK) resin, The coating layer has a thickness of 40 μm to 300 μm.

2. The insulated wire according to claim 1, wherein The ratio of the mass of the fluororesin layer to the mass of the insulated wire is 50 mass % or more.

3. The insulated wire according to claim 1 or 2, wherein: The coating layer has a relative dielectric constant of 2.9 or less.

4. The insulated wire according to any one of claims 1 to 3, wherein The partial discharge inception voltage measured at 25°C satisfies the following relationship: Partial discharge inception voltage (V) ≥ 2.2 × X + 810 X: ratio of the mass of the fluororesin layer to the mass of the insulated wire, the unit of which is mass %.

5. The insulated wire according to any one of claims 1 to 4, wherein The change rate calculated by the following formula is less than 10%, Change rate (%)=[(partial discharge inception voltage measured at 25° C.)−(partial discharge inception voltage measured at 200° C.)] / (partial discharge inception voltage measured at 25° C.)×100.

6. The insulated wire according to any one of claims 1 to 5, wherein The change rate calculated by the following formula is less than 10%, Change rate (%)=[(partial discharge inception voltage measured at 25°C after heating the insulated wire at 200°C for 1000 hours)−(partial discharge inception voltage measured at 25°C)] / (partial discharge inception voltage measured at 25°C)×100.

7. The insulated wire according to any one of claims 1 to 6, wherein The thickness of the PAEK resin layer is greater than 15 μm. The load required for power on is 1500g or more.

8. The insulated wire according to any one of claims 1 to 7, wherein The fluororesin contained in the fluororesin layer has a melt flow rate of 0.1 g / 10 minutes to 120 g / 10 minutes.

9. The insulated wire according to any one of claims 1 to 8, wherein The melting point of the fluororesin contained in the fluororesin layer is 240°C to 320°C.

10. The insulated wire according to any one of claims 1 to 9, wherein The fluororesin contained in the fluororesin layer contains a tetrafluoroethylene unit and a fluoroalkyl vinyl ether unit.

11. The insulated wire according to claim 10, wherein The content of the fluoroalkyl vinyl ether unit of the fluororesin contained in the fluororesin layer is 1.0 mol % to 30.0 mol % based on all monomer units.

12. The insulated wire according to any one of claims 1 to 9, wherein The fluororesin contained in the fluororesin layer contains tetrafluoroethylene units and hexafluoropropylene units.

13. The insulated wire according to any one of claims 1 to 12, wherein The fluororesin contained in the fluororesin layer has a functional group, and the number of the functional groups of the fluororesin is 6 The number of carbon atoms ranges from 5 to 1300.

14. The insulated wire according to any one of claims 1 to 13, wherein The fluororesin has at least one functional group selected from the group consisting of a carbonyl-containing group, an amino group, a hydroxyl group, a difluoromethyl group, an olefin group, an epoxy group, and an isocyanate group.

15. The insulated wire according to any one of claims 1 to 14, wherein The conductor is composed of at least one selected from the group consisting of copper, copper alloys, aluminum, and aluminum alloys.

16. The insulated wire according to any one of claims 1 to 15, wherein The cross-sectional shape of the conductor is any one of circular, elliptical, rectangular, square and polygonal.

17. The insulated wire according to any one of claims 1 to 16, wherein The coating layer further includes a composite resin layer, the composite resin layer is formed between the fluororesin layer and the PAEK resin layer, and contains a melt-processable fluororesin and a PAEK resin. The adhesion between the fluororesin layer and the composite resin layer, and the adhesion between the composite resin layer and the PAEK resin layer are both 0.1 N / mm or more.

18. The insulated wire according to claim 17, wherein The fluororesin contained in the composite resin layer contains a tetrafluoroethylene unit and a fluoroalkyl vinyl ether unit.

19. The insulated wire according to claim 17 or 18, wherein The fluororesin contained in the composite resin layer has a functional group, and the number of the functional groups of the fluororesin is 6 The number of carbon atoms ranges from 5 to 1300.

20. The insulated wire according to any one of claims 1 to 19, which is an industrial motor winding or a flat magnet wire.

Citation Information

Patent Citations

  • Fluorine-containing copolymer and its use

    JP2006152234A

  • Heat-shrinkable tubing for forming rectangular magnet wire coating layer, rectangular magnet wire and manufacturing method thereof, and coil

    JP2021002458A

  • Curable composition, cured product, prepreg and fiber-reinforced molded article

    WO2017122743A1

  • Insulated wire, coil, and electric / electronic apparatus

    WO2017175516A1

Cited By

  • Insulated power cable and preparation method thereof

    CN121748058A